2011
DOI: 10.1007/s13197-011-0477-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and storage stability of retort processed Chettinad chicken

Abstract: Chettinad chicken was prepared using boneless meat derived from spent hen and boiler breeder packed in retort pouches (250 g) and processed in retort at the product temperature of 121.1°C and the corresponding F 0 value of 5.2. The product was stored at ambient temperature (35±2°C) up to 180 days. The sensory scores for texture of the Chettinad chicken prepared from spent hen and broiler breeder meat decreased significantly however the scores were rated very acceptable even on 180th day. The thiobarbituric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
3
9
0
3
Order By: Relevance
“…These finding are in agreement with our study. Rajan et al (2014) reported that, no E. coli, Salmonella spp, Clostridium spp, Staphylococci spp, Streptococci spp, yeast and mould were detected in Chettinad chicken processed at high temperature (121.1°C) during its storage at ambient temperature (35±1°C).…”
Section: Discussionmentioning
confidence: 99%
“…These finding are in agreement with our study. Rajan et al (2014) reported that, no E. coli, Salmonella spp, Clostridium spp, Staphylococci spp, Streptococci spp, yeast and mould were detected in Chettinad chicken processed at high temperature (121.1°C) during its storage at ambient temperature (35±1°C).…”
Section: Discussionmentioning
confidence: 99%
“…The pH values of eel steaks in curry decreased from 6.7 to 5.8 during storage. 6.6 ± 0.1 1 6.4 ± 0.1 2 6.2 ± 0.1 3 6.1 ± 0.1 4 6.1 ± 0.1 5 6.0 ± 0.5 6 5.9± 0.1 7 5.8 ± 0.1 8 5.7 ± 0.1 Table.5 Changes in TVB-N content of eel in curry product during storage at ambient temperature The commonly observed decrease in pH might be due to degradation of proteins and liberation of free amino acids (Rajan et al, 2011). The results are in accordance with the studies conducted by Mohan et al, (2006) has reported a slight reduction in the pH of shrimp kuruma upon storage in both retort pouch and aluminium cans.In case of mackerel curry packed in retort pouch, Mallick et al, (2006) observed decrease in pH values from 5.8 to 5.43 at room temperature and 5.65 to 5.55 at 37 o C during 6 months storage of rohu in curry medium using polyester-coated tin free steel cans.…”
Section: Changes In Biochemical Characteristicsmentioning
confidence: 98%
“…Gas CO2 terbentuk karena penguraian karbohidrat menjadi unit-unit yang lebih sederhana karena aktivitas mikroba dalam proses fermentasi (Farikha dkk., 2013). Selain itu, penurunan pH dapat terjadi karena adanya degradasi protein dan pelepasan asam amino bebas (Rajan et al, 2011).…”
Section: Pengaruh Suhu Dan Waktu Sterilisasi Terhadap Nilai Mikrobiologiunclassified